STUDY OF SOIL-TRANSMITTED HELMINTHIASIS PREVALENCE IN SCHOOL CHILDREN IN SURABAYA - Amalia, Astri Nur; Prasetya, Heru (Journal of Vocational Health Studies, 2017)
Background: Soil-Transmitted Helminths infection usually occurs due to poor sanitation in the densely populated area with bad sanitation. It is transmitted by egg present in human feces then contaminate soil. Helminths infection can cause declining in health condition, nutrient, and intelligence, carbohydrate, protein and blood which in turn can disturb the patient productivity. Helminth infection can be prevented by an education and through comprehension about hygiene and environmental sanitation. Purpose: The aim of this study is to investigate the prevalence of soil-transmitted helminths infection in student grade one and two from MI Taswirul Afkar Surabaya (elementary school grade). Method: Specimen were collected from 23 feces. Macroscopic examination was conducted at Parasitology Laboratory, Faculty of Medicine, Universitas Airlangga. Result: The result from 23 samples showed that 3 (13.04%) samples were positive for Ascaris lumbricoides.Conclusion: the prevalence number of soil-transmitted helminths infection in student grade one and two from MI Taswirul Afkar Surabaya are 13.04 %, so it is important to emphasizing the role of parents in maintaining children's health, hygiene, and environmental sanitation to prevent infection.